Geography or skills: What explains Fed watchers' forecast accuracy of US monetary policy? - Helge Berger; Michael Ehrmann; Marcel Fratzscher (European Central Bank (ECB), 2006)
The paper shows that there is a substantial degree of heterogeneity in forecast accuracy among Fed watchers. Based on a novel database for 268 professional forecasters since 1999, the average forecast error of FOMC decisions varies 5 to 10 basis points between the best and worst-performers across the sample. This heterogeneity is found to be related to both the skills of analysts – such as their educational and employment backgrounds – and to geography. In particular, there is evidence that forecasters located in regions which experience more idiosyncratic economic conditions perform worse in anticipating monetary policy. Moreover, systematic forecaster heterogeneity is economically important as it leads to greater financial market volatility after FOMC meetings. Finally, Fed communication may exert an influence on forecast accuracy.
Keywords: E52; E58; G14; 330; communication; Federal Reserve; FOMC; forecast; geography; heterogeneity; monetary policy; skills; survey data; United States; Geldpolitik; Zentralbank; Ökonomen; Frühindikator; Bewertung; USA